KINERJA PERDAGANGAN LINTAS BATAS NTT-TIMOR LESTEE - Sukarna Wiranta (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2008)
The border trade between Belu Regency, West Nusa Tenggara Province, Indonesia and Republic Democratic of Timor Lestee (RDTL) become the crucial issue. It is due to the border become the illegal trading of all comodities, particularly staple foods due of its high different price of those commodities. While on the other hand, they were a big families of those people in Indonesia and Timor Lestee. The trade using the many jalan tikus (rat streets) to reach Belu which familiar to illegal trader from RDTL in order to get income. This happened after Timor Timur has separated from Indonesia. This paper aims to describe the situation of ilegal trade border between East Timor and Timor Lestee.